Faktor-Faktor Yang Mempengaruhi Return Saham Perusahaan Industri Yang Terdaftar Di BEI - Bima Dharmasetya, Tony Sudirgo (Jurnal Paradigma Akuntansi, 2022)
This research were done with a purpose to empirically examine the influence of return on equity (ROE), earning per share (EPS), debt to equity ratio (DER) dan operating cash flow toward stock return. This research uses data which collected from secondary data obtained directly from Indonesia Stock Exchange (IDX) official website. Population of this research is industry companies listed on Indonesia Stock Exchange (IDX) for the period of 2017-2019. As much as 82 companies listed on Indonesia Stock Exchange (IDX) are selected as samples in this research based on few criteria. These samples are collected using purposive sampling method. The method that is used on this research was multiple linear regression using Eviews 11 (student version) as test equipment. The result of this research indicate that return on equity (ROE) has a positive and significant effect on stock return, earning per share (EPS) has a negative and not significant effect on stock return, debt to equity ratio (DER) has a positive and not significant effect on stock return and operating cash flow has a negative and significant effect on stock return.